Graphene oxide-loaded shortening as an environmentally friendly heat transfer fluid with high thermal conductivity - Thammasit Vongsetskul (2018)
© 2017 Society of Thermal Engineers of Serbia. Graphene oxide-loaded shortening (GOS), an environmentally friendly heat transfer fluid with high thermal conductivity, was successfully prepared by mixing graphene oxide (GO) with a shortening. Scanning electron microscopy revealed that GO particles, prepared by the modified Hummer's method, dispersed well in the shortening. In addition, the latent heat of GOS decreased while their viscosity and thermal conductivity increased with increasing the amount of loaded GO. The thermal conductivity of the GOS with 4% GO was higher than that of pure shortening of ca. three times, from 0.1751 to 0.6022 W/mK, and increased with increasing temperature. The GOS started to be degraded at ca. 360 °C. After being heated and cooled at 100 °C for 100 cycles, its viscosity slightly decreased and no chemical degradation was observed. Therefore, the prepared GOS is potentially used as environmentally friendly heat transfer fluid at high temperature.